F pocket flexibility influences the tapasin dependence of two differentially disease‐associated MHC Class I proteins. Issue 4 (14th February 2015) - Abualrous, Esam T.; Fritzsche, Susanne; Hein, Zeynep; Al‐Balushi, Mohammed S.; Reinink, Peter; Boyle, Louise H.; Wellbrock, Ursula; Antoniou, Antony N.; Springer, Sebastian
<x xml:space="preserve">Abstract</x> The human MHC class I protein HLA‐B*27:05 is statistically associated with ankylosing spondylitis, unlike HLA‐B*27:09, which differs in a single amino acid in the F pocket of the peptide‐binding groove. To understand how this unique amino acid difference leads to a different behavior of the proteins in the cell, we have investigated the conformational stability of both proteins using a combination of in silico and experimental approaches. Here, we show that the binding site of B*27:05 is conformationally disordered in the absence of peptide due to a charge repulsion at the bottom of the F pocket. In agreement with this, B*27:05 requires the chaperone protein tapasin to a greater extent than the conformationally stable B*27:09 in order to remain structured and to bind peptide. Taken together, our data demonstrate a method to predict tapasin dependence and physiological behavior from the sequence and crystal structure of a particular class I allotype. Also watch the Video Abstract